"We Became Sceptics": Fear and Media Hype in General Public Narrative on the Advent of Pandemic Influenza. Issue 4 (26th July 2014) - Davis, Mark; Lohm, Davina; Flowers, Paul; Waller, Emily; Stephenson, Niamh
<x xml:space="preserve">Abstract</x> In this article, we examine the apparent resistance of publics to messages regarding pandemic influenza. The 2009 H1N1 pandemic was addressed through media: governments used print, broadcast, and digital media to advise publics to enact hygiene practices and comply with social isolation; news media took up the pandemic as a lead story. Publics, however, rated the pandemic as not serious, even before it was widely known that it was mild for most. This problem is presently constructed as complacency: where individuals are seen to lack appropriate motivation to avoid risk. We combine perspectives on media reflexivity on the part of audiences with general public interviews and focus groups in Australia and the UK, to offer an alternative explanation for complacency. Publics endorse public health advice, but are skeptical of pandemic risk communication. They exhibit critical awareness of outbreak narrative and concomitant emotions, such as fear, which are coded into media stories. We, therefore, challenge the view that publics are complacent. Instead, governments must navigate an emerging terrain of ramified and critical media consumption to shape effective risk communication in time of global health emergency.